2019
DOI: 10.1016/j.quascirev.2019.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Fluid inclusions from the deep Dead Sea sediment provide new insights on Holocene extreme microbial life

Abstract: The Dead Sea Deep Drilling Project allowed to retrieve a continuous sedimentary record spanning the two last glacial cycles. This unique archive, in such an extreme environment, has allowed for the development of new proxies and the refinement of already available paleoenvironmental studies. In particular, the interaction of the lake and sediment biosphere with elements and minerals that constitute paleoclimatic proxies has been emphasized. Although life is pushed to its extremes in the Dead Sea environment, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…2) instead suggests a bacterial origin of the WEs. Recent work on fluid inclusions allowed the retrieval of bacterial sequences in halite-dominated layers of the deep Dead Sea sediment (Thomas and Ariztegui, 2019). Our data would therefore support the development of bacteria upon archaeal necromass in the extreme environment of the Dead Sea subsurface.…”
Section: Resultssupporting
confidence: 59%
“…2) instead suggests a bacterial origin of the WEs. Recent work on fluid inclusions allowed the retrieval of bacterial sequences in halite-dominated layers of the deep Dead Sea sediment (Thomas and Ariztegui, 2019). Our data would therefore support the development of bacteria upon archaeal necromass in the extreme environment of the Dead Sea subsurface.…”
Section: Resultssupporting
confidence: 59%
“…However, none of these examples determined to what extent the identified communities represented dead, dormant, or metabolically active communities. Conversely, a recent study of Dead Sea sediments [157] illustrated a new pathway of carbon transformation in the subsurface and demonstrated how life can be maintained in extreme environments characterized by long-term isolation and minimal energetic resources.…”
Section: Dead or Alive: What Makes Up The Sedadna Pool?mentioning
confidence: 99%
“…Nevertheless, sulfate‐reducing bacteria (SRB) activity has been detected in the Dead Sea water column, springs, and sediments from sulfur isotopic analyses of sulfide and sulfate (Bishop et al., 2013; Gavrieli et al., 2001; Häusler et al., 2014; Ionescu et al., 2012; Neev & Emery, 1967; Nissenbaum & Kaplan, 1976). Thomas and Ariztegui (2019) analyzed fluid inclusions from within halite and suggested that both archaea and bacteria are involved in the sulfur cycle in the Dead Sea. Overall, the high salinity and poor organic matter content limit MSR activity in the Dead Sea (Häusler et al., 2014; Ionescu et al., 2012; Thomas & Ariztegui, 2019; Thomas et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thomas and Ariztegui (2019) analyzed fluid inclusions from within halite and suggested that both archaea and bacteria are involved in the sulfur cycle in the Dead Sea. Overall, the high salinity and poor organic matter content limit MSR activity in the Dead Sea (Häusler et al., 2014; Ionescu et al., 2012; Thomas & Ariztegui, 2019; Thomas et al., 2016).…”
Section: Introductionmentioning
confidence: 99%